INVESTIGASI MODEL PENGEMBANGAN WISATA HALAL; SEJAUH MANA PERAN RELIGIOSITAS DALAM MENCIPTAKAN KEPUASAN DAN LOYALITAS? - Hidayat, Moh. Helmi (Politeknik Ubaya, 2024)
Creating satisfaction and loyalty in the tourism business is the basis that will determine the sustainability of the business. These two variables are very important variables, even this issue is being studied among researchers, regarding what factors are the determinants in creating satisfaction and loyalty. This research is in the form of dissecting the determining factors that will create satisfaction and loyalty. This study tries to dissect whether religiosity, destination image, demographics and motivation have a big role in creating satisfaction and loyalty. To do so, researchers managed to collect as many as 177 respondents to fill out a research questionnaire. Then from the data that the researcher has obtained, the researcher analyzes the data statistically descriptive and SEM PLS to prove the hypothesis that has been made by the researcher. From this analysis the researcher got the result that religiosity, destination image, demographics have a positive and significant effect on satisfaction, while motivation is not significant on satisfaction. Besides that, religiosity, destination image, demographics can indirectly influence the loyalty variable through satisfaction. Religiosity can be a moderating variable for the relationship between demographics and satisfaction. Finally, the satisfaction variable has a significant effect on loyalty.